Anterior Cervical Discectomy and Fusion (ACDF Results in VC5-6) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
We conducted a retrospective study to compare the clinical and radiological results of anterior cervical discectomy and fusion (ACDF)ACDF is chosen for milder cases, while ACCF is not done for CSR. Localized OPLL is usually asymptomatic at the very beginning. Patients’ symptoms are aggravated by disc herniation at the same intervertebral space level or due to neurological symptoms caused by disc injury because of recent trauma. For this reason, ACDF may achieve the same efficacy as ACCF by resecting the herniated disc and OPLL at the intervertebral space level with much less surgical injury than ACCF. The limited surgical exposure and the adhesion of the OPLL to the dura make the operation more difficult. Therefore, ACDF was considered to perform only when the preoperative CT scan showed that the OPLL did not extend to the entire posterior margin of the vertebrae [1,2,3].In this study, we found that the volume of blood loss and duration of surgical procedure were significantly less in patients undergoing ACDF than in patients undergoing ACCF. The majority of previous studies were in accordance with our results. This difference is because ACCF requires resecting the corresponding vertebral body and the adjacent disc, which is more traumatic. However, the duration of the ACDF surgical procedure was significantly longer than that of the ACCF procedure, which was contrary to our study. He believed that performing ACDF to remove osteophytes from the intervertebral space is time-consuming and more technically challenging. The reason why many scholars perform ACCF is that the difficulty of ACDF is much greater than that of ACCF. The limited surgical exposure and the adhesion of the OPLL to the dura make it difficult to decompress sufficiently. However, when the technical learning curve of ACDF is mature, it is a more advantageous surgical method [1,3,7].ACCF and ACDF not only relieves compression in the spinal cord but also reconstructs the physiological parameters of the cervical spine through careful distraction of the intervertebral space showed that ACDF had better maintenance of disc space height and greater improvements in cervical lordosis. Our study corresponded with it. Compared with patients who underwent ACCF, the postoperative disc space height was significantly improved in those who underwent ACDF. However, disc space height dropped slightly in both groups when they came to review and the ACCF group decreased more than the ACDF group. The reduced height of the treated disc space was partly due to postoperative subsidence of implant settling and then migrating to the endplates. The subsidence rate of implant in our study was 5.2% in the ACDF group and 28.4% in the ACCF group. We thought that the difference of subsidence rate was related to the shape of both ends of the implant. [2,4,5]. The main causes of abnormalities in patients who undergo ACCF may be related to excessive damage to the vertebral endplate and the rigid effect of the titanium cage. The contact surface of the titanium cage is sharper. Under the action of stress, it is more likely to protrude to the cancellous bone to form subsidence. However, the cage used in ACDF has a relatively large effective contact surface, which disperses the stress of adjacent vertebrae and is more advantageous in the maintenance of intervertebral height. The subsidence rate was low in ACDF in our study, but there was still a decrease in the height of the intervertebral space at the last follow-up. We speculated that intraoperative distraction of the intervertebral space and then postoperative gravity on the cervical spine contributed to this condition. In addition, the thickness of the removed endplate also had a significant effect on the subsidence of the cage after fusion surgery.19 We suggest preserving the bony endplate as much as possible to prevent cage subsidence when scraping the endplate cartilage [6,7].